Anti-tau conformational scFv MC1 antibody efficiently reduces pathological tau species in adult JNPL3 mice - Francesca Vitale; Luca Giliberto; Santiago Ruiz; Kristen Steslow; Philippe Marambaud; Cristina d’Abramo (Acta Neuropathologica Communications, 2018)
Abstract Tau, the main component of the neurofibrillary tangles (NFTs), is an attractive target for immunotherapy in Alzheimer’s disease (AD) and other tauopathies. MC1/Alz50 are currently the only antibodies targeting a disease-specific conformational modification of tau. Passive immunization experiments using intra-peritoneal injections have previously shown that MC1 is effective at reducing tau pathology in the forebrain of tau transgenic JNPL3 mice. In order to reach a long-term and sustained brain delivery, and avoid multiple injection protocols, we tested the efficacy of the single-chain variable fragment of MC1 (scFv-MC1) to reduce tau pathology in the same animal model, with focus on brain regional differences. ScFv-MC1 was cloned into an AAV delivery system and was directly injected into the hippocampus of adult JNPL3 mice. Specific promoters were employed to selectively target neurons or astrocytes for scFv-MC1 expression. ScFv-MC1 was able to decrease soluble, oligomeric and insoluble tau species, in our model. The effect was evident in the cortex, hippocampus and hindbrain. The astrocytic machinery appeared more efficient than the neuronal, with significant reduction of pathology in areas distant from the site of injection. To our knowledge, this is the first evidence that an anti-tau conformational scFv antibody, delivered directly into the mouse adult brain, is able to reduce pathological tau, providing further insight into the nature of immunotherapy strategies.